1987
DOI: 10.1186/1297-9686-19-2-181
|View full text |Cite
|
Sign up to set email alerts
|

Assortative mating and artificial selection: a second appraisal

Abstract: SummaryThe impact on selection response of the positive assortative mating of selected parents was determined for a 2 generation cycle. Relative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…As indicated by Smith and Hammond (1987), a combination of restricted parent contributions and high selection accuracy offers a potential for PAM to increase variance that has not yet been fully investigated. Furthermore, in tree breeding, studies of selection and PAM would be more relevant if they also focused on a selected PP, in addition to the behaviour over the entire BP.…”
Section: Effect Of Selection and Mating On Genetic Variancementioning
confidence: 98%
See 2 more Smart Citations
“…As indicated by Smith and Hammond (1987), a combination of restricted parent contributions and high selection accuracy offers a potential for PAM to increase variance that has not yet been fully investigated. Furthermore, in tree breeding, studies of selection and PAM would be more relevant if they also focused on a selected PP, in addition to the behaviour over the entire BP.…”
Section: Effect Of Selection and Mating On Genetic Variancementioning
confidence: 98%
“…Smith and Hammond 1987;Shepherd and Kinghorn 1994) have reported that the effect of PAM on the BP additive mean increases when selection includes information from relatives, i.e. combined-index selection or selection on BLUP breeding values.…”
Section: Breeding Population Mean and Variancementioning
confidence: 98%
See 1 more Smart Citation
“…Even if the distribution of breeding values in the selected parents departs significantly from normality, segregation tends to reduce this departure. Interestingly, Smith and Hammond (1987)…”
Section: E Within and Between-family Contributions To Additive Genetic Variancementioning
confidence: 99%
“…Different methods have been proposed for maximizing selection response at the same level of inbreeding, i.e. to restrict the number of close relatives selected (NICHOLAS and SMITH 1983), to use false high heritability estimates in the genetic evaluation (GRUNDY and HILL 1993), to use assortative (SMITH and HAMMOND 1986) or compensatory (GRUNDY et al 1994) matings, to adjust estimated breeding values for the relationship with the already selected ones (GODDARD and SMITH 1990), to avoid matings of related individuals (TORO and PEREZ-ENCISO 1990), or to use factorial rather than hierarchical matings (WOOLLIAMS 1989;LEITCH et al 1994). QUINTON and SMITH (1995) compared the merits of these methods using stochastic simulation; they concluded that none of the methods was best over all conditions, and that the use of false high heritabilities, or adjusted estimated breeding values with the relationships, does not seem to be recommended; besides, mating together those individuals with the lowest relationship has little effect on the accumulated inbreeding.…”
Section: Introductionmentioning
confidence: 99%